ANALISIS PENDEKATAN INKUIRI PADA PEMBELAJARAN MATEMATIKA BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Nadia Juniyanti Sri Indah Purba; Ni Putu Gita Widiyani; Andri Anugrahana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Inclusive education provides equal learning space for all students, including children with special needs. This study aims to determine the effectiveness of the inquiry approach for students with special needs in mathematics lessons in inclusive schools. The inquiry approach was chosen because it encourages student activity through exploration and direct learning experiences, which are in accordance with the learning characteristics of students with special needs. This study uses a qualitative descriptive method with observation techniques for students with special needs and interviews with teachers at one of the inclusive schools in Yogyakarta. The results of the study indicate that the inquiry approach with the use of concrete media, intensive guidance, and inclusive group work strategies is effective for understanding mathematical concepts for students with special needs. The conclusion of this study is that an adaptive and contextual inquiry approach is able to create an inclusive, collaborative learning environment and support the cognitive and social-emotional development of students with special needs.